油品组成对蜗杆副承载能力的影响 - 李学雷; 徐钢涛; 潘卫彬; 戚文正 (Jixie chuandong)
Based on the test results of warm gear drive lubricated by 15 types of oil,the effect of oils with different additives and varied contents is studied on anti-scuffing capacity of warm gear pair.The following conclusions are obtained:（1） the anti-scuffing capacity of worm gear pair could be lowered considerably if unsuitable oil additives are used.（2） the anti-scuffing capacity of worm gear pair is enhanced by the increase of anti-wear additive in the oil.（3） the anti-scuffing capacity of warm gear pair could also be enhanced if the content of extreme pressure（EP） additives is increased,but the effect was not so good as anti-wear additives.